2018
DOI: 10.1097/md.0000000000012573
|View full text |Cite
|
Sign up to set email alerts
|

The effect and safety of dexmedetomidine added to ropivacaine in brachial plexus block

Abstract: Background:Dexmedetomidine has been used as an adjuvanty added to local anesthetics to prolong analgesia following peripheral nerve blockade. The aim of this meta-analysis was to investigate the effect and safety of dexmedetomidine added to ropivacaine in brachial plexus block (BPB).Methods:A search strategy was created to identify eligible randomized clinical trial (RCT) in PubMed, Embase, and The Cochrane Library (updated May, 2018). The methodologic quality for each included study was evaluated using the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 26 publications
5
22
0
Order By: Relevance
“…Dexmedetomidine (DEX), a potent and selective α 2 adrenoceptor agonist, was recently shown to prolong analgesic duration when added to local anaesthetics in regional anaesthesia . This effect is related to the enhancement of hyperpolarization‐activation cation currents, which prevents the nerve from returning to resting membrane potential from a hyperpolarized state and subsequent firing .…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 4 more Smart Citations
“…Dexmedetomidine (DEX), a potent and selective α 2 adrenoceptor agonist, was recently shown to prolong analgesic duration when added to local anaesthetics in regional anaesthesia . This effect is related to the enhancement of hyperpolarization‐activation cation currents, which prevents the nerve from returning to resting membrane potential from a hyperpolarized state and subsequent firing .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…DEX has greater affinity for the α 2 adrenergic receptor than clonidine and a greater inhibitory effect on neuronal action potential; thus, it has superior analgesic qualities as a BPB adjuvant . Several studies have demonstrated increased duration and improved quality of analgesia when DEX was added to local anaesthetics for various indications . A 30‐40 mL mixture of 0.5% ropivacaine and 1 µg/kg DEX injection has been investigated for regional anaesthesia with BPB, and the addition of DEX was found to prolong the duration of sensory and motor blockade, and reduce the time required for onset of action, but the effect was not associated with the DEX dose .…”
Section: What Is New and Conclusionmentioning
confidence: 99%
See 3 more Smart Citations